Measurements of Solid Velocity in a Pilot-Scale Geldart's Group B Circulating Fluidized Bed Using a Radioactive Particle Tracking Technique - Tribedi T.; Pillajetti P.; Kumari R.; Pant H.J.; Tiwari P.; Upadhyay R.K. (My University, 2025)
Circulating fluidized bed (CFB) is used for a wide range of gas-solid reactions. However, most of the data reported on CFBs are for Geldart's group A particles, although the applications of Geldart's group B CFBs are numerous. In the current work, the solid flow field is deciphered in a pilot-plant-scale Geldart's group B CFB riser. Solid motion is tracked by using a radioactive particle tracking technique. The data are reported in a fully developed flow region of 0.1 m diameter and 6.5 m height CFB riser at different inlet gas velocities (7.6-9.2 m/s) and solid fluxes (100-200 kg/m2 s). The different flow quantities such as mean axial and radial velocities, root-mean-square velocities, granular temperature, and turbulent intensities are calculated for all the cases. It is observed that solid motion predominantly lies in the axial direction. The probability distribution function of instantaneous solid velocity shows wider distribution near the wall as compared to the center of the riser. This shows that the probability of mesoscale metastable structure formation increases while moving from the center to the wall. Furthermore, the results show that the mean solid velocity largely depends on gas-solid interactions. However, for the fluctuating velocity, both gas-solid and solid-solid interactions are critical. The results indicate that the solid turbulent intensity in Geldart's group B riser is significantly higher than that in the group A riser. Hence, solid velocity fluctuations are higher in the group B riser. © 2022 American Chemical Society.